A Study of Service Speed and Servicescape as a Basic Strategy to Improve Loyalty by Evaluating Customer Satisfaction at PT. Bank Mandiri Persero (Solo Branch) - Siti Fatonah; Tulus Haryono; Pramesty Wahyu Istyaningsih (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine and analyze empirically the effect of service speed and servicescape on customer satisfaction and loyalty at PT. Bank Mandiri Persero (Solo Branch). The analysis technique used was the validity test and reliability test, linearity test, regression analysis, path analysis, t test, F test, determination coefficient test and correlation analysis. Hypothesis Test Results indicated that service speed has a positive and significant effect on customer satisfaction and servicescape has a positive and significant effect on customer satisfaction. Service speed has a positive and significant effect on customer loyalty. Servicescape has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. The results of F in the second equation showed that the value of F = 288.445, with a significance of 0.000 0.05, so it can be concluded together that the independent variables have a significant effect on customer loyalty at PT. Bank Mandiri Persero (Solo Branch). The results of the R2 value can be explained by the variable service speed, servicescape, and customer satisfaction as an intervening variable of 92.6% and the remaining 7.4% explained by other variables outside the research model in the form of interest rates, service quality, and so on. The results of the path analysis showed that: the indirect effect of service speed on loyalty is an effective route. The indirect effect of the servicescape on loyalty is an effective route. Based on these results, the use of customer satisfaction mediation is proven, so it is expected that PT. Bank Mandiri Persero (Solo Branch) pays more attention to the level of customer satisfaction in order to increase customer loyalty.